2018
DOI: 10.1158/1078-0432.ccr-18-0290
|View full text |Cite
|
Sign up to set email alerts
|

Curation of the Pancreatic Ductal Adenocarcinoma Subset of the Cancer Genome Atlas Is Essential for Accurate Conclusions about Survival-Related Molecular Mechanisms

Abstract: Publicly available databases, for example, The Cancer Genome Atlas (TCGA), containing clinical and molecular data from many patients are useful in validating the contribution of particular genes to disease mechanisms and in forming novel hypotheses relating to clinical outcomes. The impact of key drivers of cancer progression can be assessed by segregating a patient cohort by certain molecular features and constructing survival plots using the associated clinical data. However, conclusions drawn from this stra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
58
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 13 publications
(8 reference statements)
3
58
0
Order By: Relevance
“…The normalized and annotated genes for TCGA was obtained from Broad GDAC Firehose database 6 . We have removed 29 non-PDAC samples from TCGA during validation as our classifier was trained using PDAC samples ( Peran et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The normalized and annotated genes for TCGA was obtained from Broad GDAC Firehose database 6 . We have removed 29 non-PDAC samples from TCGA during validation as our classifier was trained using PDAC samples ( Peran et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…To determine the association of key genes with survival in PC, we performed survival analysis using the TCGA database 7 . The survival analysis was performed on PDAC mRNA of 150 patients [excluding samples related to normal tissues and non-PDAC tissues ( Peran et al, 2018 )]. Survival analysis was performed on the basis of individual mRNA expression using the Kaplan-Meier (K-M) approach ( Kaplan and Meier, 1958 ).…”
Section: Methodsmentioning
confidence: 99%
“…All of these models have robust predictive ability, but they are not accurate enough, as most of them are derived from the single TCGA-PAAD dataset. A study showed that the failure to exclude non-PDAC samples from the TCGA-PAAD cohort might lead to false conclusions regarding the prognostic value of biomarkers [ 23 ]. Furthermore, the inclusion a large number of genes (up to 36) hinders the translation of predictive models into clinical application.…”
Section: Introductionmentioning
confidence: 99%
“…Second, most researchers did not perform preanalysis case selection, whereas using an uncurated TCGA dataset without attention to sample characteristics can lead to false associations and undermine the application of the conclusions . The patients with the diagnosis of non‐HCC liver cancer (cholangiocarcinoma), pathological metastasis, and postsurgical residual carcinoma, the history of neoadjuvant treatment, and too short survival time are considered to have distinct biological procedures and progression mechanisms, and should be excluded from the prognostic analysis . Third, most studies performed the analysis by mixing resectable and unresectable cancers .…”
Section: Introductionmentioning
confidence: 99%